2003
DOI: 10.1046/j.1365-294x.2003.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and molecular rates of subterranean aquatic Stenasellid Isopods with a peri‐Tyrrhenian distribution

Abstract: The subterranean Isopods belonging to the genus Stenasellus have an interesting disjunct distribution in the peri-Tyrrhenian area with morphologically closely related taxa occurring in Sardinia, Corsica, Tuscany and in the Pyrenees phreatic and interstitial waters. Because the dispersal capacities of these organisms are limited, their distribution has been associated traditionally with the tectonic events leading to the separation of the Sardinia-Corsica microplate from the Pyrenees and its subsequent movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 43 publications
4
103
1
Order By: Relevance
“…Aquatic isopods of the genus Stenasellus are highly adapted to subterranean life, they spend their whole life cycle in subsurface freshwaters and active dispersal can only happen when such a habitat is continuous [33]. Given these characteristics, it was not unexpected to find molecular relationships (regardless of the markers employed) to be remarkably in agreement with the palaeogeography of the area.…”
Section: Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic isopods of the genus Stenasellus are highly adapted to subterranean life, they spend their whole life cycle in subsurface freshwaters and active dispersal can only happen when such a habitat is continuous [33]. Given these characteristics, it was not unexpected to find molecular relationships (regardless of the markers employed) to be remarkably in agreement with the palaeogeography of the area.…”
Section: Eventsmentioning
confidence: 99%
“…Subsequent within-island evolution has been documented molecularly but very often it did not produce appreciable morphological differences. Illustrative is the case of the subterranean isopod Stenasellus [33,40,56]. The few known populations of this crustacean are virtually indistinguishable morphologically and yet they are deeply divergent from one another at both mitochondrial and nuclear loci.…”
Section: Comparisons To Other Insular Systemsmentioning
confidence: 99%
“…(Drummond et al, 2011). It has been reported that the evolutionary rates of the COI genes in the Crustacea vary from 1.66%/Ma to 3.0%/Ma (Ketmaier et al, 2003), although a rate of approximately 2.0%/Ma is broadly used for the molecular clock of vertebrate mitochondrial cytochrome b (e.g., Rocha et al, 2005;Fernandes et al, 2012;Rapson et al, 2012). Because there is no reliable temporal calibration point directly applicable to our data, we used a rate of 2.5%/Ma as a representative value, which was reported to be the COI divergence rate in a stenasellid isopod (Ketmaier et al, 2003).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Inferred expansions were dated following the expression T = τ/2μk, where τ is the estimated number of generations since the expansion, μ is the mutation rate per site per generation and k is the sequence length. We assumed a mutation rate of 1% per lineage per million years (average estimate reported in Ketmaier et al 2003) and a mean generation time of 2 yr (see Freire et al 2002).…”
Section: Samplingmentioning
confidence: 99%